Antecedents and Consequences of Brand Love with Moderated By Memories - Rahmawati Azizah MT (Jurnal Economia, 2019)
AbstractThis research aims to examine the effect of perceived brand quality and brand personality on brand fondness with memories as moderator. This study examines the effect of independent variables on dependent variable with memories as moderating variable. The subject in this research were students, civil servants, professionals (nuns, accountants), entrepreneurs, private employees whom are users of Asus brand laptop in Indonesia. The sample were chosen by using nonprobability sampling technique namely purposive sampling. The instrument of this study was online questionnaire and the gathered data is analyzed by using multiple regression analysis. The finding of this study explains that perceived brand quality and brand personality have a positive effect on brand fondness. Brand fondness has a positive effect on brand loyalty and active engagement. The finding on moderation variables explains that memories are not proven to moderate the effect between perceived brand quality and brand fondness, it means that the magnitude of memory as a moderating variable has nothing to do with the relationship between independent variables and dependent variable. In addition, the finding of variable memories proved to moderate the effect between brand personality and brand fondness, it means that it will strongly influence the relationship between brand personality and brand fondness when the variable memory is high, otherwise it will become weak when the variable memory is low. Keywords: Perceived brand quality, brand personality, brand love, brand loyalty, active engagement, memories.Anteseden dan Konsekuensi Kecintaan Merek dengan Dimoderasi oleh KenanganAbstrakPenelitian ini bertujuan untuk menguji pengaruh kualitas merek yang dipersepsikan dan kepribadian merek pada kecintaan merek dengan kenangan sebagai pemoderasi. Subjek dalam penelitian ini adalah mahasiswa, PNS, profesional (suster, akuntan), wiraswasta, karyawan swasta yang merupakan pengguna laptop merek Asus di Indoensia. Sampel yang dipilih menggunakan teknik nonprobability sampling dengan jenis purposive sampling. Instrumen penelitian ini adalah kuesioner yang dibuat secara online dan dianalisis dengan analisis regresi berganda. Penelitian ini menemukan bahwa kualitas merek yang dipersepsikan dan kepribadian merek memiliki pengaruh positif pada kecintaan merek. Kecintaan merek memiliki pengaruh positif pada loyalitas merek dan keterlibatan aktif. Temuan pada variabel moderasi, kenangan tidak terbukti memoderasi pengaruh antara kualitas merek yang dipersepsikan dan kecintaan merek, artinya bahwa tinggi atau rendahnya kenangan sebagai variabel moderasi tidak ada kaitannya pada hubungan antara variabel independen dan variabel dependen. Selain itu, temuan variabel kenangan terbukti memoderasi pengaruh antara kepribadian merek dan kecintaan merek, artinya bahwa akan menjadi kuat pengaruh kepribadian merek pada kecintaan merek ketika variabel kenangan tinggi, dan sebaliknya akan menjadi lemah ketika variabel kenangan rendah. Kata kunci: Kualitas merek yang dipersepsikan, kepribadian merek, kecintaan merek, loyalitas merek, keterlibatan aktif, kenangan positif.